THE MACROFUNGI DIVERSITY AND THEIR POTENTIAL UTILIZATION IN TANGALE NATURE RESERVE GORONTALO PROVINCE - Arini, Diah Irawati Dwi; Christita, Margaretta; Kinho, Julianus (BERITA BIOLOGI, 2019)
Tangale Nature reserve is a conservation area located in Gorontalo that have the biodiversity typical of Wallacea bioregion including macroscopic fungi. The purpose of this study was to identify the fungal species diversity found in the Tangale Nature reserve as well as its potential use, considering that the information on species diversity of fungi in the Wallacea region is very limited. This research was conducted using the cruise method by identifying macroscopic fungi along the hiking trail of Tangale Nature Reserve. The macroscopic fungi were observed for its morphological characteristic include the colour, diameter, surface of the veil, the shape of the stem, the length and diameter of the stem, the lamella, including ring and pore, type of lamella and the type of volva. The research recorded the substrates and the location where the fungus was found. Data were analyzed descriptively qualitative. The results of the research identified 28 species of macroscopic fungi that included to the division Ascomycota and Basidiomycota. It belongs to 16 families and 8 orders  are Pezizales, Agaricales, Auriculariales, Boletales, Cantharellales, Gomphales, Polyporales, dan Russulales. Based on place to grow as much as 57,14% were found growing on decaying wood and 42,86% found growing in the soil/litter. Based on the potential of use, it has identified four species of mushrooms potentially as edible mushroom are Pleurotus ostreatus,  Auricularia auricula, Ramaria formosa, and Polyporus arcularius. 11 species of mushrooms potentially as medicinal mushroom are Calvatia craniiformis, Scleroderma citrinum, Lenzites betulina, Microporus flabelliformis, Coriolus versicolor, Microporus xanthopus, and Albatrellus confluens.